2009
DOI: 10.1056/nejmoa0804883
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Consequences of Kidney Donation

Abstract: BACKGROUND The long-term renal consequences of kidney donation by a living donor are attracting increased appropriate interest. The overall evidence suggests that living kidney donors have survival similar to that of nondonors and that their risk of end-stage renal disease (ESRD) is not increased. Previous studies have included relatively small numbers of donors and a brief follow-up period. METHODS We ascertained the vital status and lifetime risk of ESRD in 3698 kidney donors who donated kidneys during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

49
755
7
26

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 931 publications
(851 citation statements)
references
References 25 publications
49
755
7
26
Order By: Relevance
“…1,2 Recent long-term prospective data suggest that overall survival and risk of developing chronic kidney disease in kidney donors is similar to the general population. In addition, kidney donors experience excellent quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Recent long-term prospective data suggest that overall survival and risk of developing chronic kidney disease in kidney donors is similar to the general population. In addition, kidney donors experience excellent quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, kidney donors experience excellent quality of life. 1 Although living donors represent more than half of the renal transplants performed in North America, there is still a wide gap between the need and availability of transplantable organs. Transplant centres are using several strategies to increase organ availability, including broadening medical acceptance criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Allaying some fear regarding donor risk was a recent single center study that reported survival of kidney donors was similar to that of controls matched for age, gender, and race (7).…”
mentioning
confidence: 99%
“…It is known that renal reserve capacity is maintained except in those with a high BMI and old age (15), and proteinuria or albuminuria may increase over time from surgery (7,16 -20). It is also known that in mostly white donor populations, between 0.1 to 1.1% develop ESRD, roughly the same as the general population (5,7,(21)(22)(23). This information comes from identification of donors added to the UNOS transplant waitlist and does not include those starting dialysis but not listed for transplant.…”
mentioning
confidence: 99%
“…In one study where kidney donors were followed for approximately 4 decades, less than 15 % of donors had a measured GFR by iohexol clearance of less than 60 mL/min per 1.73 m 2 , and none had a GFR of less than 30 mL/min per 1.73 m 2 . Approximately 13 % of kidney donors had some degree of microalbuminuria, but none of the patients had both microalbuminuria and a suboptimal GFR [30]. The rate of decline of GFR after donation remained within the expected values observed in healthy individuals, suggesting that there was no added underlying pathophysiologic process other than those observed with aging alone.…”
Section: Donor Kidney Function and Its Implications To The Donormentioning
confidence: 72%